Role of sugammadex in the treatment of anaphylaxis due to rocuronium in children: Extrapolation from adult and animal reports. Issue 6 (7th March 2022) - Ghimire, Anuranjan; Olbrecht, Vanessa A.; Tobias, Joseph D.
Abstract: Allergic reactions are generalized hypersensitivity processes triggered by different antigenic stimuli, resulting in the end effect of mast cell degranulation and adverse physiologic effects. During the perioperative period, the most commonly identified agents include antibiotics, neuromuscular blocking agents (rocuronium and succinylcholine), chlorhexidine, and iodinated dyes for radiologic imaging. Sugammadex is a novel agent for the reversal of neuromuscular blockade achieved with rocuronium or vecuronium. Its unique mechanism of action, whereby it encapsulates and forms a one‐to‐one complex with rocuronium, has led to its anecdotal use as an adjunct in the treatment of anaphylactic and anaphylactoid reactions following rocuronium. The current manuscript discusses the potential use of sugammadex in the treatment of allergic reactions following the administration of rocuronium, reviews previous anecdotal reports of its use in these scenarios, and provides recommendations for future care.